1982
DOI: 10.1007/bf01391449
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of chronic portal?Systemic encephalopathy with vegetable and animal protein diets

Abstract: A controlled crossover clinical comparison of 40-g/day and 80-g/day vegetable protein diets vs a 40-g/day meat protein diet plus neomycin-milk of magnesia (as control therapy) was performed on 10 cirrhotic patients with mild chronic portal-systemic encephalopathy. The 40-g vegetable protein diet had a high fiber volume and contained low methionine and low aromatic amino acids. The 80-g vegetable protein diet was rich in branched-chain amino acids and fiber, with a similar content of sulfur-containing amino aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(31 citation statements)
references
References 13 publications
0
30
0
1
Order By: Relevance
“…In protein-intolerant pa tients vegetable proteins are superior to pro teins derived from fish, milk or meat. In three controlled studies a vegetable diet was better tolerated than a diet which also included meat [55][56][57], Other studies did no show these faborable effects. The beneficial effects of a vegetable diet on the protein tolerance of pa tients with HE cannot be explained by the amino acid compositions of the proteins alone.…”
Section: Diet In Hementioning
confidence: 95%
“…In protein-intolerant pa tients vegetable proteins are superior to pro teins derived from fish, milk or meat. In three controlled studies a vegetable diet was better tolerated than a diet which also included meat [55][56][57], Other studies did no show these faborable effects. The beneficial effects of a vegetable diet on the protein tolerance of pa tients with HE cannot be explained by the amino acid compositions of the proteins alone.…”
Section: Diet In Hementioning
confidence: 95%
“…Moreover, a drop in urinary nitrogen output and in fasted blood ammonia concentration are well-known effects of the consumption of vegetable-protein diets (Conn, 1993). The in¯uence of vegetable protein on the blood ammonia concentration has been used in the treatment of pathologies such as chronic encephalopathy, in which the blood ammonia level is increased (Bianci et al, 1993;Uribe et al, 1982). In Western countries, animal products supply about two thirds of the food protein, whereas plant protein foods contribute to two thirds of the world supply (Young and Pellet, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…To date, only 7 studies have been completed that examined vegetable protein versus animal protein and their effects on hepatic encephalopathy [36,37,41,[52][53][54][55] . Six of the studies showed positive results on vegetable protein, including improved HE, improved mental status, larger bowel across daily meals, whereas frail and prefrail individuals tend to skew their protein intake toward noon meal while consuming significantly less at other meals [61] .…”
Section: Vegetable Versus Animal Protein As a Treatment And Preventiomentioning
confidence: 99%
“…In a short-term bed rest study, healthy older men were given a protein supplement of 20 g after breakfast and before sleep versus no supplement. Results movements, EEG improvements, a trend toward positive nitrogen balance, improved branched-chain amino acid to aromatic amino acid ratio, lower urine nitrogen concentrations, and lower plasma ammonia levels [36,37,41,[52][53][54] . One of the studies showed no significant differences in grade of HE, nitrogen balance, or plasma amino acids [55] .…”
mentioning
confidence: 97%